BMP-7 Upregulates Id2 Through the MAPK Signaling Pathway to Improve Diabetic Tubulointerstitial Fibrosis and the Intervention of Oxymatrine - Xiao, Yawen; Liang, Dan; Li, Zhiyang; Feng, Zhaowei; Yuan, Zhiping; Zhang, Fan; Wang, Yuanyuan; Zhou, Yuxia; Shi, Mingjun; Liu, Lingling; Xiao, Ying; Guo, Bing (Frontiers in Pharmacology, 2022)
Diabetic kidney disease is one of the most serious microvascular complications of diabetes. It progresses irreversibly to end-stage renal disease if left untreated. Bone morphogenetic protein (BMP)-7 is a negative regulator of organ fibrosis and may also play an essential role in tubulointerstitial fibrosis. This study aimed to investigate the precise role and potential molecular mechanisms of BMP-7 in the progression of diabetic nephropathy. In this study, BMP-7 was overexpressed in vivo after the replication of the diabetic rat model using streptozotocin. The results showed that BMP-7 inhibited the phosphorylation of related mitogen-activated protein kinase (MAPK) pathways while upregulating the inhibitor of differentiation (Id2) expression and effectively ameliorated pathological renal injury. Further in vitro validation showed that the inhibition of the phosphorylation of MAPKs at a high glucose concentration in renal tubular epithelial cells was followed by the upregulation of Id2 protein expression, suggesting that BMP-7 could improve diabetic nephropathy by upregulating Id2 protein levels through the BMP-7–MAPK signaling pathway. Previous laboratory studies found that oxymatrine improved renal fibrotic lesions. However, the exact mechanism is unclear. The present study showed that oxymatrine treatment in a diabetic rat model upregulated BMP-7 protein expression and inhibited MAPK pathway protein phosphorylation levels. These results suggested that oxymatrine improved the epithelial-to-mesenchymal transition process in the early stage of diabetic kidney disease by regulating the BMP-7–MAPK pathway and ameliorated renal tubulointerstitial fibrosis.